2012
DOI: 10.1038/emboj.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

EBV and human microRNAs co-target oncogenic and apoptotic viral and human genes during latency

Abstract: Epstein–Barr virus (EBV) controls gene expression to transform human B cells and maintain viral latency. High‐throughput sequencing and crosslinking immunoprecipitation (HITS‐CLIP) identified mRNA targets of 44 EBV and 310 human microRNAs (miRNAs) in Jijoye (Latency III) EBV‐transformed B cells. While 25% of total cellular miRNAs are viral, only three viral mRNAs, all latent transcripts, are targeted. Thus, miRNAs do not control the latent/lytic switch by targeting EBV lytic genes. Unexpectedly, 90% of the 166… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
287
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(301 citation statements)
references
References 109 publications
(200 reference statements)
12
287
0
2
Order By: Relevance
“…4D). In contrast, LMP1, a known target of EBV miRNAs (43,44), was down-regulated as expected (Fig. 4D).…”
Section: Ebv Mirnas Inhibit Mhc Class I Antigen Processing and Presenmentioning
confidence: 77%
“…4D). In contrast, LMP1, a known target of EBV miRNAs (43,44), was down-regulated as expected (Fig. 4D).…”
Section: Ebv Mirnas Inhibit Mhc Class I Antigen Processing and Presenmentioning
confidence: 77%
“…The let-7a expression and IL-6 production is significantly decreased by the depletion of E2F2 or NF-κB in immune-stimulated cells (Cho et al, 2015). MiR-222, miR-223, the miR-17~92 cluster, and miR-155 are associated with the differentiation of T cells (Riley et al, 2012;Poole and Sinclair, 2015;Saki et al, 2015). EBV-encoded EBNA2 induces the expression of miR-21, consequently promoting B cell transformation and driving the antiviral immune response (Rosato et al, 2012;Zhu et al, 2013).…”
Section: Ebv Latent Proteins Dysregulate Host Mirnas To Regulate the mentioning
confidence: 99%
“…The roles of these BHRF1 miRNAs were unclear until recent in vitro studies using viral knockouts in lymphoblastoid cell lines (LCLs), a widely used cellular model of latency III EBV infection, revealed that the BHRF1 miRNAs cooperate to enhance B cell expansion, reduce levels of latent gene expression, and possibly also inhibit apoptosis (10-12). Additionally, as circumstantial evidence for the roles of these miRNAs, studies that comprehensively examined the targets of EBV miRNAs have shown that BHRF1 miRNAs bind a number of targets involved in proliferation, latent gene expression, and regulation of apoptosis (13,14).…”
Section: Over 90% Of the Adult Human Population Is Chronically Infectmentioning
confidence: 99%